Clinical and pathological assessment of the calystegines in Ipomoea carnea in a goat model - Daniel Cook; Bryan L. Stegelmeier; Dale R. Gardner; Franklin Riet-Correa; Clinton A. Stonecipher; Kevin D. Welch (Toxicon, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Predicting Aberrant Fc-fusion Protein Pharmacokinetics from In Silico Structural Properties and Physiologically Based Pharmacokinetic (PBPK) Modeling - Danilo Tomasoni; Alessio Paris; Roberto Visintainer; Kevin D. Cook; Aochiu Chen; Isabel Figueroa; Veena A. Thomas; Luca Marchetti (The AAPS Journal, 2026)
The fusion of therapeutic proteins to the Fc domain of monoclonal antibodies (mAbs) generally improves the proteins' pharmacokinetic (PK) characteristics, extending in vivo half-lives due to the binding of the Fc domain to the FcRn receptor. Yet, several of these Fc-fusion biologics have been observed to have unexpected rapid clearance associated with non-specific off-target binding. Variability in non-specific clearance is often challenging to predict, not well understood, and ultimately can delay the drug development process. In this investigation, we present a computational approach leveraging in silico protein structural properties to extend a physiologically based pharmacokinetic (PBPK) model of mAbs validated on in vivo plasma PK profiles in mice. Selected model parameters affecting protein half-life have been scaled by analytical functions of a panel of calculated in silico protein properties identified by a novel and ad hoc symbolic regression procedure. The resulting extended model has been successfully validated against an independent set of protein plasma PKs, indicating that it can generalize to novel biologics of the same class. Moreover, the extended PBPK model has a median absolute average fold error (AAFE) of 1.18 (min = 1.09; max = 1.51), where values less than 2 typically indicate a good fit. The results enable the de-risking of aberrant PK behaviors, ultimately leading to the selection of Fc-fusion proteins with increased therapeutic value for patients.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

DNA data (genome skims and metabarcodes) paired with chemical data demonstrate utility for retrospective analysis of forage linked to fatal poisoning of cattle - Daniel Cook; Brandon Kocurek; Clint Stonecipher; Kevin D. Welch; Dale R. Gardner; Mark Mammel; Elizabeth Reed; Padmini Ramachandran; David Erickson; Seth Commichaux; Andrea Ottesen (Toxicon, 2025)

The actions of varenicline on alkaloids from Conium maculatum (poison hemlock), Lupinus sulphureus (sulphur lupine) and Nicotiana glauca (tree tobacco) - Benedict T. Green; Stephen T. Lee; Kevin D. Welch; Daniel Cook; Clinton A. Stonecipher (Toxicon, 2024)

The evaluation of earwax as a noninvasive specimen to determine livestock exposure to death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Kevin D. Welch; Daniel Cook (Toxicon, 2024)

The use of earwax to determine livestock exposure to teratogenic lupine - Clinton A. Stonecipher; Stephen T. Lee; Kevin D. Welch; Kristian R. Valles; Daniel Cook (Toxicon, 2024)

Comparison of the acute toxicity of zygacine versus zygadenine - Kevin D. Welch; Dale R. Gardner; Stephen T. Lee; Clint A. Stonecipher; Daniel Cook (Toxicon, 2024)

Acute death as a result of poisoning tropical (Bos taurus indicus) but not temperate (Bos taurus taurus) cattle after oral dosing with Lupinus leucophyllus (velvet lupine) - Benedict T. Green; Kevin D. Welch; Stephen T. Lee; T. Zane Davis; Clinton A. Stonecipher; Bryan L. Stegelmeier; Daniel Cook (Toxicon, 2024)

Ruminant metabolism of zygacine, the major toxic alkaloid in foothill death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Benedict T. Green; Kevin D. Welch; Dale R. Gardner; Daniel Cook (Toxicon, 2024)

The ectomycorrhizal fungus Paxillus ammoniavirescens influences the effects of salinity on loblolly pine in response to potassium availability - Benjamin D. Rose; Marissa A. Dellinger; Clancy P. Larmour; Mira I. Polishook; Maria I. Higuita‐Aguirre; Summi Dutta; Rachel L. Cook; Sabine D. Zimmermann; Kevin Garcia (Environmental Microbiology, 2024)
Salinity is an increasing problem in coastal areas affected by saltwater intrusion, with deleterious effects on tree health and forest growth. Ectomycorrhizal (ECM) fungi may improve the salinity tolerance of host trees, but the impact of external potassium (K + ) availability on these effects is still unclear. Here, we performed several experiments with the ECM fungus Paxillus ammoniavirescens and loblolly pine ( Pinus taeda L.) in axenic and symbiotic conditions at limited or sufficient K + and increasing sodium (Na + ) concentrations. Growth rate, biomass, nutrient content, and K + transporter expression levels were recorded for the fungus, and the colonization rate, root development parameters, biomass, and shoot nutrient accumulation were determined for mycorrhizal and non‐mycorrhizal plants. P. ammoniavirescens was tolerant to high salinity, although growth and nutrient concentrations varied with K + availability and increasing Na + exposure. While loblolly pine root growth and development decreased with increasing salinity, ECM colonization was unaffected by pine response to salinity. The mycorrhizal influence on loblolly pine salinity response was strongly dependent on external K + availability. This study reveals that P. ammoniavirescens can reduce Na + accumulation of salt‐exposed loblolly pine, but this effect depends on external K + availability.

PCB126 exposure during pregnancy alters maternal and fetal gene expression - Cetewayo S. Rashid; Joshua D. Preston; Sara Y. Ngo Tenlep; Marissa K. Cook; Eric M. Blalock; Changcheng Zhou; Hollie I. Swanson; Kevin J. Pearson (Reproductive Toxicology, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Links between Indo-Pacific climate variability and drought in the Monsoon Asia Drought Atlas - Caroline C. Ummenhofer; Rosanne D. D’Arrigo; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climate Dynamics, 2013)

Influence of Phenological Stage on Swainsonine and Endophyte Concentrations in Oxytropis sericea - Daniel Cook; Lei Shi; Dale R. Gardner; James A. Pfister; Daniel Grum; Kevin D. Welch; Michael H. Ralphs (Journal of Chemical Ecology, 2012)

Swainsoninine Concentrations and Endophyte Amounts of Undifilum oxytropis in Different Plant Parts of Oxytropis sericea - Daniel Cook; Dale R. Gardner; Michael H. Ralphs; James A. Pfister; Kevin D. Welch; Benedict T. Green (Journal of Chemical Ecology, 2009)

The Biogeographical Distribution of Duncecap Larkspur (Delphinium occidentale) Chemotypes and Their Potential Toxicity - Daniel Cook; Dale R. Gardner; James A. Pfister; Kevin D. Welch; Benedict T. Green; Stephen T. Lee (Journal of Chemical Ecology, 2009)